Back Cover: Electrochemical Radical Borylation of Aryl Iodides (Chin. J. Chem. 4/2019). Issue 4 (15th March 2019) - Hong, Junting; Liu, Qianyi; Li, Feng; Bai, Guangcan; Liu, Guoquan; Li, Man; Nayal, Onkar S.; Fu, Xuefeng; Mo, Fanyang
Abstract : The back cover picture shows an electrochemical strategy for the borylation of aryl iodides via a radical pathway using current as a driving force. This method features mild reaction conditions, good functional groups tolerance, and prompt reaction time. EPR, CV and DPV experiments verified the formation of aryl radicals in this electrochemical borylation reaction, and the current plays an important role in the generation of radical intermediate. More details are discussed in the article by Mo et al. on page 347–351. Abstract : The back cover picture shows an electrochemical strategy for the borylation of aryl iodides via a radical pathway using current as a driving force. This method features mild reaction conditions, good functional groups tolerance, and prompt reaction time. EPR, CV and DPV experiments verified the formation of aryl radicals in this electrochemical borylation reaction, and the current plays an important role in the generation of radical intermediate. More details are discussed in the article by Mo et al. on page 347–351.